Experimental and Numerical Thermal Transient Behavior of Chips in a Liquid Channel During Loss of Pumping Power - Tso, C. P.; Tou, K. W.; Bhowmik, H. (2004)
Both transient and steady-state experiments are performed to study the single-phase heat transfer characteristics on an array of four in-line, flush-mounted simulated chips in a vertical rectangular channel. Water is the coolant media, and the flow covers the wide range of laminar regimes with the Reynolds number based on heat source length, from 800 to 2625. The effect of heat fluxes, coolant flow rates, and geometric parameters (such as chip configuration number) are investigated. The operation is extended to study the transient natural convection during an accidental stoppage of coolant flow due to loss of pumping power Results compare favorably with those obtained from three-dimensional numerical calculations. The transient correlation recommended is Nu(l)=0.3 (Fo)(-0.2) (Ra-l(*))(1/4).